Advances in CRISPR-Cas based genome engineering. (March 2017) - Katrekar, Dhruva; Hu, Michael; Mali, Prashant
Abstract : Development of the CRISPR-Cas systems has catalyzed rapid advancements in the field of genome engineering. Recently, the technology has seen various new developments, including the successful use in RNA-targeting, the development of more precise genome editing reagents, and breakthroughs in applications to gene therapy and regenerative medicine. These rapid developments, when coupled with its ease of use and high efficiency, are spurring widespread adoption of the technique, and in fact, use of CRISPR-Cas technology towards gene therapy clinical trials is already underway. In this review, we provide an overview of the CRISPR-Cas systems for genome engineering, and in particular, stress key toolsets and methodologies that we believe will have particularly broad impact on both basic science and translational research. Highlights: CRISPR-Cas is enabling programmable genetic, epigenetic and transcriptomic engineering. CRISPR-Cas is enabling high throughput biology via applications in screening methodologies. Novel HDR-independent targeting methods are enabling precision genomic edits. Application to organoid systems is enabling generation of human disease models. CRISPR-Cas9 based clinical trials are underway.